Firm survival and location preference: evidence from Mexico city - Víctor Reyes; Manuel Suárez (Heliyon, 2022)
The aim of this research is to find if there is a relationship between firm location and road class, and whether location decisions regarding road class affect the probability of firm survival. We examine the location of 35 selected types of businesses in Mexico City in four road classes. We develop a location preference coefficient that indicates whether the number of businesses that locate within a road class is above or below the expected number. With this calculation we can not only see what class of road each business type prefers, but also the degree of this preference. We find certain business types to prefer only specific road classes while others have a higher variation in their preference. We then run a logistic regression model to predict firm survival after a 5-year period. We find that location on the road class preferred by the business type to be the variable that most contributes to the probability of firm survival.